Surface Application of Lime on a Guava Orchard in Production - Medeiros Correa, Marcio Cleber de; Natale, William; Prado, Renato de Mello [UNESP]; Banzatto, David Ariovaldo [UNESP]; Queiroz, Ronialison Fernandes; Camacho da Silva, Marcos Antonio (Soc Brasileira De Ciencia Do Solo, 2018)
Several complications can arise, either directly or indirectly, from implementation of measures to correct soil acidity in established fruit orchards, such as impaired roots, lower root volume, risk of plant infection, propagation of diseases, promotion of pest development (especially nematodes), and soil disaggregation and compaction. These factors can have a negative effect on crop yield. Therefore, it becomes critical to implement an effective method of neutralizing soil acidity, especially at the level of the tree roots. To assess the effect that the rates and forms of limestone applied on the soil surface have on soil fertility and on nutrition and yield of guava, an experiment was conducted in a commercial orchard. A randomized block experimental design was implemented with three replicates consisting of two forms of limestone [common limestone with relative neutralizing value (RNV) = 80 % and calcined limestone with RNV = 131 %], which were applied at five different rates (0, 0.5, 1, 1.5, and 2 times the recommended rate to raise the V value to 70 %), without incorporation. Liming with common or calcined limestone caused a drop in soil acidity in the 0.00-0.10 m layer at 6, 12, and 24 months after application. Soil acidity decreased in the 0.10-0.20 m layer at 6 and 12 months after use of calcined limestone, and at 24 months after liming with the common form of limestone. The chemical composition (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, Zn) of leaves was not affected at 14 months after surface liming treatments, nor the chemical composition of fruit at 20 months after the treatments. Guava yield was not affected by surface liming.
Keywords: soil acidity; limestone; perennial crop; fruticulture; Psidium guajava